Structural Dynamics of HIV Risk, Resilience and Response (Social Aspects of HIV,, 2018)
This book examines the structural dynamics of HIV among populations at heightened vulnerability to infection as the result of stigma, discrimination and marginalization. It first examines how the socio-structural context shapes HIV risk and how affected populations and national governments and programs have responded to these structural constraints. Chapters focus on structural determinants of HIV risk among transgender women in Guatemala, migrant workers in Mexico, Nigeria and Vietnam, and people who inject drugs in Tanzania. Next, the book examines resilience and community empowerment and mobilization among key populations such as female sex workers in the Dominican Republic and India, and young women and girls in Botswana, Malawi and Mozambique. A third set of chapters explores how national responses to HIV have addressed the role of structural factors in diverse political, geographic and epidemic settings including: Brazil, South Africa, Ukraine and the USA. Ultimately, effective and sustainable responses to HIV among marginalized groups must be grounded in an in-depth understanding of the factors that create vulnerability and risk and impede access to services. Throughout, this book brings together a rigorous social science research perspective with a strong rights-based approach to inform improvements in HIV programs and policies. It offers new insights into how to better address HIV and the health and human rights of historically excluded communities and groups.